2014
DOI: 10.1093/intqhc/mzu023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of certification and accreditation on quality management in 4 clinical services in 73 European hospitals

Abstract: ObjectiveTo investigate the relationship between ISO 9001 certification, healthcare accreditation and quality management in European hospitals.DesignA mixed method multi-level cross-sectional design in seven countries. External teams assessed clinical services on the use of quality management systems, illustrated by four clinical pathways.Setting and ParticipantsSeventy-three acute care hospitals with a total of 291 services managing acute myocardial infarction (AMI), hip fracture, stroke and obstetric deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 7 publications
3
81
0
13
Order By: Relevance
“…[23,30,31] In other systematic reviews, accreditation programs are consistently found to facilitate improvements in medical institutions and healthcare quality. [32][33][34] The standards included in this study are intended to determine whether the goals and purpose of the accreditation system are being achieved well. In the future, it will be necessary to carry out additional research to determine how accreditation affects patients' well-being as well as research to evaluate outcome indicators, and cost-effectiveness studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23,30,31] In other systematic reviews, accreditation programs are consistently found to facilitate improvements in medical institutions and healthcare quality. [32][33][34] The standards included in this study are intended to determine whether the goals and purpose of the accreditation system are being achieved well. In the future, it will be necessary to carry out additional research to determine how accreditation affects patients' well-being as well as research to evaluate outcome indicators, and cost-effectiveness studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some empirical studies found that accreditation improves patient safety, including mortality, morbidity, and the incidence of infection, [32,[36][37][38][39] and this needs to be applied to domestic research. However, the ability to generalize from the results of this study is limited because the history of Korea's accreditation system is short and few relevant studies exist.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of services provided in hospital institutions, the fast pace of work and the possible lack of resources, together with an increased technological progress, may represent barriers that go beyond this and other strategies that aim at quality of care by means of accreditation 11,12 . Even if hospital accreditation has its limitations, this quality management system results in improvements related to patient safety, from the interviewed managers' point of view, and in benefits to quality of care:…”
Section: Not To Mention the Benefits [Of Accreditation] To The Patienmentioning
confidence: 99%
“…Statements made by QM1H2 and QMH3 show that accreditation is an element that brings safety to users cared for at the hospital, and consequently, it is something that supports quality of care as a result. This is important, as patient/user safety has been one of the most discussed topics in the health care sphere, both in practice and in scientific fields, including in the establishment of international targets, which include prevention and management of adverse outcomes related to care services, among others 12 . It is worth remembering that safety in care is a diktat already provided at the first certification level of national accreditation 4 .…”
Section: Benefits and Difficulties Of Hospital Accreditationmentioning
confidence: 99%
“…A eficácia dos processos pode ser alcançada a partir de indicadores e de treinamentos para os trabalhadores, fazendo com que os processos sejam desenvolvidos com base na sua real necessidade 20 . Shaw et al 18 afirmam que a acreditação está associada com os sistemas utilizados pelos hospitais para a segurança do paciente. Seu aprimoramento se relaciona com a implantação bem-sucedida de iniciativas de melhoria da qualidade 6 .…”
unclassified